Impact of Government Expenditure in Education, Health Sectors and Financial Inclusion on Human Development in Indonesia - Mulia Simatupang; Bonar M Sinaga; Sri Hartoyo; Harianto Harianto (Budapest International Research and Critics University, 2022)
The aim of this paper in to assess the impact of financial inclusion and government expenditure in education and health sectors in order to increase human development index. Government expenditure has important role to achieve and increase economic growth and welfare. Government fiscal policy spending in education and health sectors are kind of significant government policy to increase human development. This study found that financial inclusion has important contribution to human development. Financial inclusion has positive effect to the human development index components along with government expenditures in education and health sector. As the consequences, in the future the government should prioritize its budget in education and health sector in order to increase human resources quality in Indonesia.